The reception of Galatians 2:20 in the Patristic period and in the Reformation - A. van de Beek (Acta Theologica)
This article explores the reception of Galatians 2:20 in the Patristic period, and in the Reformation by Luther and Calvin. As it turns out, the interpretation of the verse does not fit into popular notions of their theological traditions. Authors from traditions as different as the Alexandrians and the Antiochians, or Eastern and Western, do not interpret this verse as expected, when taking into account the theological framework in which later generations placed the communities wherein the former exegetes lived. This is especially striking when comparing Luther and Calvin. The result is an exhortation for further research in reception history. It might well fundamentally challenge frameworks of historical research.